South African saxophone compositions: exploring the process of creating new music for saxophone through the lens of artistic research and performer-composer collaboration - Mc Clure, Josie (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMus)--Stellenbosch University, 2023.